Layered cake booking system - Chia, Ka Choon (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Kek Lapis Sarawak is a well famous cake product at Sarawak and yet none of any mobile application available for the cake booking system. As mobile devices are widely used today, this is the huge opportunity to set the business through application. The purpose of this project is to develop an android based mobile booking application. To go to some specific shop to just make a booking is time consuming, therefore using an application will case the booking process and save time. Besides that, this application also serves as an alternative marketing tool.